Biologia floral e polinização em canola (Brassica napus L.) por abelhas africanizadas (Hymenoptera: Apidae) em duas épocas de semeadura - Chambó, Emerson Dechechi (2013)
The objectives of the present study are: to evaluate the pollination by Africanized honeybees (Apis mellifera) over the production and quality of rapeseed (Brassica napus L.) hybrids Hyola 61 and 433 sown on two distinct dates; to evaluate floral biology and female fertility; to determine which insects are pollinators; to identify insect flower foraging patterns in relation to specific meteorological variables. In the first study (conducted in the Western part of the southern state of Paraná, Brazil), the treatments consisted of combinations of two rapeseed hybrids (Hyola 61 and Hyola 433), three pollination tests (uncovered area, covered area without insects, and covered area with an Africanized A. mellifera colony) and two different sowing dates (05/25/2011 and 06/25/2011). The variables analyzed were grain yield, grain yield per plant and seeds per pod, number of seeds per pod and pods per plant, thousand grain weight, vigor, germination and oil content in seeds. In the second study we analyzed the morphology, stigma receptivity, pollen feasibility and germinability, scent releasing areas, and the frequency that the Africanized honeybees visited the flowers, as well as female fertility, which was studied considering the two sowing dates. The frequency of the visitor insects observed during the first 10 minutes of each time, from 8:00 to 17:00h, showed that each insect remained one minute in front of the marked plant. In each analyses session there were recorded: the number of visitation to the rapeseed flowers by each pollinator and the resources collected by the Africanized honeybees; the number of flowers visited by the Apis mellifera in a minute; the number of flowers visited by the Apis mellifera in only one plant in one minute; and finally how much time the A. mellifera spent on the flowers. In this study the analyses were made through different generalized linear models. Rapeseed production can be increased in terms of its productive components with the presence of Africanized bees during flowering time.Hybrids may have attenuated their production losses, due to cross-pollination by Africanized bees, when conditions were less favorable for the development of culture, namely, when sown were done on 06/25/2011. The foraging activity by Africanized bees may be limited due to weather conditions, causing decreased cross-pollination by potential pollinators, especially the Africanized A. mellifera honeybee. Rapeseed hybrids respond differently depending on the sowing date, and the short-cycled Hyola 433 hybrid is the most adequate when sowing occurs in less favorable weather conditions. Rapeseed flowers are hemaphroditic and are arranged in racemose inflorescences, with duration of 48 hours. The ovary has, on average, between 24.72 ± 2.8 eggs. The petals measure between 14.75 ± 0.96 mm of length and 7.81 ±0.77 mm of diameter. The youngest flowers, aging between 3 and 9 hours and 24 and 33 hours have pollen grains with the ability to release the pollen tube and larger stigma capacity (P < 0.05) in relation to the button stage in pre-antheses and flowers between 48 and 51 hours old. Pollen viability present in the corbicula of Africanized honeybees was 97%. Osmophores were found on the entire corolla and anthers. The seed/egg ratio was 74%. The flowers of the hybrids Hyola 61 and 433 are protandric and have mechanisms that allow for the occurrence of allogamy. The data suggest the occurrence of a mixed reproductive mechanism in B. napus, considering the ample reproductive flexibility of the species, with a significant rate of egg development in seeds, even when there is no cross-pollination. The Africanized honeybees were the most abundant pollinating insects (89%) among all flower visitors, and the nectar collectors were the most frequent (90%) in the culture. The Africanized honeybees visited 12.9 ± 1.40 flowers in one minute and 2.96 ± 1.09 flowers on only one plant in one minute. The time that honeybees spent on the rapeseed flowers was 4.2 ± 1.6 seconds. The abundance of floral visitors followed the variation of abiotic factors throughout the day, especially the temperature, relative humidity, wind speed, and solar radiation. The Africanized bees were more active than the other pollinators at different times of the day and they also foraged more intensely on the Hyola 433 hybrid than on the Hyola 61 hybrid; the latter was more attractive to the other floral visitors.